URGENSI PENCATATAN PERKAWINAN DALAM KORIDOR HUKUM ISLAM - Muhammad Ikhwan (STAI Darul Quran Payakumbuh, 2017)
This research is purposed to discuss a solution to a dualism law of marriage. As Moslems, execution of marriage surely is based on the regulations arranged by Islam. As Indonesian citizens, the execution of marriage based on the regulations stirred by our country. As an example, there is a recording marriage. In Islam, marriage is regarded as legal if it has fulfilled is its principle and requirement. In order to have a law power, based on Indonesian law, a marriage must be recorded. The recording marriage also tells and about the duty and right of husband and wife and their duty to their children in case of unwanted cases in the household. The law dualism becomes a conflict in the society in which some people neglect the regulation on the recording of marriage. Therefore, the record of marriage is studied in two approaches namely; religious approach and the positive law approach. In the religious approach, fiqh studies about the rule of qiyas awla which focuses on a problem of debt transaction as stated in the Qur’an, surah Annisa, verse 282 which produces a duty of marriage record. The law positive approach stated that law realizes a discipline in the middle of society. Therefore, the recording of marriage must be done. Based on the approaches, the dualism of marriage law can be vanished and can be summarized about Indonesian Islamic Law. It states that the recording of marriage is considered a duty.